Evaluation of the effects of mental visualisation training in sport with regard to karate shotokan fighters specializing in kata - Piepiora, P.; Witkowski, K.; Migasiewicz, J. (Journal of Combat Sports and Martial Arts, 2017)
Background and aim: Mental visualisation training makes use of human imagination in such a way as to program a person`s mind to perform a movement task in the best possible manner. The aim of this article is to evaluate the effects of mental visualisation training in sport with regard to karate shotokan fighters. Material and methods: 20 karate shotokan fighters - members of the Lower Silesia team competing in kata events - were purposefully selected for the study. The age of those studied ranged between 18 and 39 years. They had training experience of 5 to 20 years and were ranked from the 1st to the 5th dan. The fighters performed an exercise consisting in visualising their participation in a kata event. The empirical research was performed using the diagnostic survey method and the research material was collected by means of a specially prepared survey questionnaire. Results: Before commencing mental visualisation training the study participants evaluated all the areas of their mental preparation at a medium level (3). After one month one area received a very high score, four of them - high scores and two of them - medium scores. After two months one area received a very high score and the remaining ones - high scores. After three months six areas received very high scores and one area - a high score, but only marginally short of a very high score. Conclusions: Over a period of two months a trend tow rds positive effects of mental visualisation training was noted. The full effects were achieved after three months of practice.